'It has saved thousands of lives, so why change it?' Content analysis of objections to cervical screening programme changes in Australia. Issue 2 (13th February 2018) - Obermair, Helena M; Dodd, Rachael H; Bonner, Carissa; Jansen, Jesse; McCaffery, Kirsten
Abstract : Objectives: The incidence and mortality of cervical cancer have halved since introduction of the Australian cervical screening programme in 1991, involving 2-yearly Pap smears from ages 18–69 years. In 2017, the programme changed to 5- yearly primary human papillomavirus (HPV) testing for women aged 25–74 years. This study investigated reasons for opposition to the renewed screening programme within the open-ended comments of an online petition, 'Stop May 1st Changes to Pap Smears—Save Women's Lives', opposing the changes, which received over 70 000 signatures and almost 20 000 comments. Methods: Content analysis of a random sample of 2000 comments, reflecting 10% of the 19 633 comments posted in February–March 2017. Results: Nineteen codes were identified, reflecting four themes: (1) valuing women's health and rights, (2) political statements, (3) concerns about healthcare funding cuts and (4) opposition to specific components of the new screening programme. The most prevalent codes were: placing value on women's health (33%), concerns about increasing screening intervals (17%) and opposition to the changes related to personal experiences with cervical cancer or cervical abnormalities (15%). Concern about the key change in technology (HPV testing instead of Pap smears) was expressed in less than 3% of comments, and some opposition to the changes from health professionals was noted. Conclusions: Screening changes within this selected group were perceived as threatening women's health, as a political policy created by male decision-makers and as a cost-cutting exercise. Many commenters were concerned about increased screening intervals and later screening onset, but little opposition was expressed regarding the testing technology itself. This analysis may inform public education and communication strategies for future changes to cervical screening programmes internationally, to pre-emptively address specific concerns about the changes.